Analysis Of Phthalates Via Spectrophotometry In Environmental Samples Using Non-Ionic Silicone Surfactant Mediated Cloud Point Extraction - Ooi, Pei Wan (2017)
Determination of phthalates in environmental matrices become crucial in recent years due to the growing international concern about the health effects of phthalates. In the present study, a greener method based on cloud point extraction was developed for the extraction of selected phthalates in environmental samples using non-ionic silicone surfactant of DC193C